Cementless Total HIP Arthroplasty Using Biolox®Delta Ceramic-on-Ceramic Bearing in Patients with Osteonecrosis of the Femoral Head. Issue 2 (23rd March 2016) - Lim, Seung-Jae; Kim, Sang-Min; Kim, Dong-Wook; Moon, Young-Wan; Park, Youn-Soo
Purpose: The purpose of this study was to evaluate the results of cementless total hip arthroplasty (THA) using a 32 mm or larger Biolox®delta ceramic-on-ceramic (CoC) bearing in patients with osteonecrosis of the femoral head after a minimum of 5 years of follow-up. Materials and methods: We retrospectively analysed 44 patients (53 hips) who underwent cementless THA using Biolox®delta CoC bearing. There were 33 men (40 hips) and 11 women (13 hips) with the mean age of 49 years. A 36 mm head was used in 42 (79%) of 53 hips and a 32 mm head was used in 11 hips with smaller acetabular shells. The mean duration of follow-up was 5.3 years (range 5-6 years). Results: The mean Harris Hip Score improved from 50 points preoperatively to 97 points at final follow-up (p<0.001). All acetabular and femoral components showed radiographic evidence of osseointegration. No osteolysis was observed. No patients sustained ceramic fracture. An audible hip noise was identified in 2 (4%) of the 53 hips (1 squeaking and 1 clicking). Survivorship with revision for any reason at a minimum of 5 years was 100% in the best-case scenario and 95 % in the worst-case scenario. Conclusions: The minimum 5-year results of cementless THA using a 32 mm or larger Biolox®delta CoC bearing in patients with osteonecrosis of the femoral head were encouraging with excellent survivorship. However, it was also found that the risk of noise development remains even for the new alumina matrix composite ceramic.